Integrative proteomic-transcriptomic analysis revealed the lifestyles of Lactobacillus paracasei H4-11 and Kluyveromyces marxianus L1-1 under co-cultivation conditions - Na Liu; Likang Qin; Haiying Zeng; Anyan Wen; Song Miao (Food Science and Human Wellness)
Compared with the rice-acid soup inoculated with single starter, the synergistically intensified rice-acid soup inoculated with Lactobacillus paracasei H4-11 (L. paracasei H4-11) and Kluyveromyces marxianus L1-1 (K. marxianus L1-1) contained more flavor compounds. Organic acids mainly included L-lactic acid and the main volatile flavor component was ethyl acetate. Moreover, the signal intensity of astringency and bitterness and the total concentration of volatile sulfur compounds were reduced. The combined analysis results of RNA sequencing (RNA-seq) technology and 4D label-free quantitative (4D LFQ) proteomics explained the flavor formation pathways in rice-acid soup inoculated with L. paracasei H4-11 and K. marxianus L1-1. In L. paracasei H4-11, L-lactate dehydrogenase, phosphoglucomutase, acetate kinase, alcohol dehydrogenase and acetyl-CoA were up-regulated and D-lactate dehydrogenase and N-Acetyltransferase were down-regulated. In K. marxianus L1-1, Acetyl-CoA, acetaldehyde dehydrogenase, acyl-coenzyme A, N-acetyltransferase, and L-lactate dehydrogenase were up-regulated and hexokinase, alcohol dehydrogenase, and alcohol O-acetyltransferase were down-regulated. The above up-regulation and down-regulation synergistically promoted the formation of characteristic flavor compounds (mainly L-lactic acid and ethyl acetate). Enzyme-linked immunoassay (ELISA) and parallel reaction monitoring (PRM) quantitative analysis respectively verified that 5 key metabolic enzymes and 27 proteins in L. paracasei H4-11 and K. marxianus L1-1 were associated with the characteristic flavor of rice-acid soup, as confirmed by the quantitative results of 4D LFQ.